2010
DOI: 10.1007/s11707-011-0161-6
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic release by indigenous bacteria Bacillus cereus from aquifer sediments at Datong Basin, northern China

Abstract: Endemic arsenic poisoning due to long-term drinking of high arsenic groundwater has been reported in Datong Basin, northern China. To investigate the effects of microbial activities on arsenic mobilization in contaminated aquifers, Bacillus cereus (B. cereus) isolated from high arsenic aquifer sediments of the basin was used in our microcosm experiments. The arsenic concentration in the treatment with both bacteria and sodium citrate or glucose had a rapid increase in the first 18 d, and then, it declined. Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…At the end of incubations, dissolved As concentration generally kept constant, demonstrating that the release of As was not obvious due to the limited bacterial activity (2.0e3.5 nmol/L ATP). It showed that the activity of bacteria had a significant effect on the release of As from the sediment (Xie et al, 2011).…”
Section: Release and Transformation Of Sedimentary Asmentioning
confidence: 99%
“…At the end of incubations, dissolved As concentration generally kept constant, demonstrating that the release of As was not obvious due to the limited bacterial activity (2.0e3.5 nmol/L ATP). It showed that the activity of bacteria had a significant effect on the release of As from the sediment (Xie et al, 2011).…”
Section: Release and Transformation Of Sedimentary Asmentioning
confidence: 99%
“…The organisms were cultivated in nutrient broth medium (1 % peptone, 0.3 % beef extract, and 0.5 % sodium chloride) at 25 ± 1°C in darkness (Xie et al 2011) to middle exponential phase for the following experiments.…”
Section: Biological Materials and Culture Conditionsmentioning
confidence: 99%
“…In addition, more and more studies demonstrated that microorganisms play a significant role in geochemical behaviour of arsenic (Bachate et al 2009;Duan et al 2009;Macur et al 2001;Wang et al 2010;Xie and Wang 2009;Xie et al 2009aXie et al , 2011. As(III) can be oxidized to As(V) by chemoautotrophic arsenite oxidizer and heterotrophic arsenite oxidizer, or As(V) can be reduced to As(III) by dissimilatory arsenate-respiring prokaryote (Oremland and Stolz 2003;Sohrin et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, presence of Bacillus spp. in Ascontaminated groundwater of Bengal basin and other alluvial aquifers as well in various polluted environment and their As transformation abilities have been well documented [17,[42][43][44][45]. Dissimilatory reduction of As 5+ by Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%